Toplu Konut Alanları İle Kent Parkları İçerisindeki Çocuk Oyun Alanlarının Karşılaştırılması - Chamberlin, Ayşegül Olcar (Fen Bilimleri Enstitüsü, 1998)
Bu çalışmanın amacı toplu konut alanı ile kent parkı içinde yer alan çocuk oyun alanlarının karşılaştırmalı bir değerlendirmesini yapmaktır. Üç örnek alan seçilmiştir. Bunlardan ilki öğretim ve gelir seviyesinin en yüksek olduğu Ataşehir toplu konut alanında, ikinci olarakta gelir ve eğitim seviyelerinin yüksek ve orta olduğu komşuluk ünitesi içinde yer alan Demokrasi Parkı içinde ve son olarakta gelir ve eğitim seviyesinin orta ve düşük olduğu komşuluk ünitesinde ki Zeytinburnu Sahil Parkı düzenlemesi içinde yer almaktadır. Oyun alanlarının hepsi de geleneksel tarzda ve yaklaşık olarak 4-12 yaş gurubuna hitap etmektedir. Seçilen örnek alanlarda 150' si ebeveyn ve 150' si çocuklar olmak üzere toplam 300 kişiyle anket yapılmıştır. Çocuklara ve yetişkinler için farklı anket formları hazırlanmıştır. Yetişkinler ile yapılan anketin içerdiği bölümler:. Kullanıcı ebevenlerinin özelliklerinin saptanması.. Tercih nedenleri.. Ebeveynlerin oyun alanlarını kullanım sıklarının değerlendirilmesi.. Oyun alanı tasarımının ve seçilen konumun güvenliğinin değerlendirilmesi.. Fonksiyonların yeterliliğinin değerlendirilmesi.. Bakım ve temizliğin değerlendirilmesi.. Diğer oyun alanlarının kullanım sıklığı ve mevcut oyun alanının diğerleriyle karşılaştırılması. Çocuklar ile yapılan anketin içerdiği bölümler: Kullanıcı özelliklerinin saptanması. Tercih nedenlerinin saptanması. Oyun alanının kullanım sıklığının değerlendirilmesi. Alana kiminle geldiği ve zamanını kimlerle geçirdiği. Alanda ki boşluk ve doluluğun değerlendirilmesi. En çok sevilen oyun aletlerinin ve aktivitelerin belirlenmesi. Bitkilendirmenin değerlendirilmesi. Algılanan gürültü ve gürültü nedenlerinin değerlendirilmesi. Diğer oyun alanlarının kullanım sıklığı ve mevcut oyun alanı ile karşılaştırılması. Çocukların yapmak istedikleri ve eksikliklerini duydukları aktiviteler. Kendi tasarladıkları oyun alanı sitilleri. Yukarıda belirtilen anket bölümlerinden yaralanılarak bağımlı ve bağımsız değişkenler oluşturulmuş ve bunlar arasında çapraz tablolar oluşturularak korelasyon ilişkilerine bakılmıştır. Ortaya çıkan sonuçlara göre; bakım ve temizlik işlerinin Hizmet AŞ. tarafından üstlenildiği Ataşehir' de ki oyun alanlarının bakım ve temizliği, bakım ve temizliği belediyelere ait Zeytinburnu ve Demokrasi parkında ki oyun alanlarına oranla çok daha iyi durumda oluğu gözlemlenmiştir. Belediyelerimiz parkların bakım ve temizlik işleriyle ilgilenmemelerinden dolaya bir sürü emek ve para harcanarak yapılan oyun alanları kullanılamayacak derecede kötü bir duruma gelmeye mahkûmdur. Bir de buna komşuluk ünitelerinde ki parkların miktar olarak ve fonksiyonel içeriklerinin her yaş gurubundan çocuğa hitap etmemesi de eklenirse çocuklara sosyal, bedenel ve zihinsel gelişimleri için yeterli olanak sağlanmamaktadır. Bunun değiştirilmesi için devlet bu konuya daha ciddi bir şekilde yaklaşmalı ve halkın desteğide alınmalıdır.

The aim of this thesis is to evaluate the differences and similarities between playgrounds in the park and in the site area. For this purpose three examples were chosen (all of which were traditional playgrounds) in the Istanbul area. The first was a playground in Ataşehir site area whose level of income and education was the highest of the ones surveyed. It was targetted at children in the age ranges of 2-6 and 7-15. The second was a playground in Democracy Park (targetted in the age ranges of 4-7 and 8-15) whose level of income and education was in the middle to high bracket. The third was located by the sea in Zeytinburnu park whose level of education and income was in the middle to low bracket. A questionaire was conducted which sampled 150 children and an equal number of adults across the three playgrounds. Table 6. 1: Data concerning parent education levels in the residential areas. Table 6.2: Data concerning income levels in the residential areas (nb. All figures all in Turkish Lira.) Two different kinds of questionaire were prepared - one for children and one for adults. The questionaire form for adults sought information in the following areas:. Personal details: age, sex, marital status, number of children, occupation, income. Reason for coming. Frequency of playground usage: type of house resided in by sample parents, places where their children play generally, freqi'- ;cy and length of time sample parents take their children to the playground and on which days and which hours they generally bring their children. XVI . Security: their opinion of the style and location of the playground and whether or not it is suitable for children's security.. Adequacy of facilities: play facilities, recreational facilities for adults.. Upkeep and cleanliness. Suitability of playground for age group. Usage of other playgrounds. Comparision of the playground with others. The questionaire form for children asked quesitons in the following areas: The personal details of users: sex, age, class in school, education level of parents Reasons for coming.. Frequency of playground usage: number of previous visits, frequency of visits, on which days and which hours, length of time spent in the playground. With whom do they come, with whom do they spend their time in the playground. How full the playground is: their opinion of how empty the playground is, level of crowding, freedom of movement.. Activities and play facilities which they enjoy most. Their evaluation of planting in the playground area: amount of playground touched by sunlight, their appreciation of the plants present in the playground, whether or not these plants make them ( ie. The children) feel uncomfortable, the number of plants that they can recognize, which plants would they like to choose for the playground given the chance.. The types and the amount of noise which they recognize in the playground.. Frequency of other playground usage.. Their comparison of the subject playground with others.. What activities they feel are lacking in the playground and what other things would they like to do.. The type of playground they would plan. Seven independent variables were looked for in the questionaire for adults:. Sex. Number of children. Occupation. Level of education. Income per month. Whether or not they have a garden. Adequacy of playground facilities Dependent variables for adults:. The frequency of playground usage. Reason for coming. At which times do they come. Security of playground' s location. Reasons for the insecurity of playground's location XVII . Security of playground' s plan. Adult's opinion concerning the adequacy of the playground's recreational facilities. Adult's opinion concerning the upkeep and cleanliness of the playground. For which age group is this playground suitable. Whether or not they take their children to other playgrounds.. Comparison of subject playground with others Twelve independent variables were looked for in the children's questionaire: Location of playground Sex Age Level of parents' education Whether they go to school or not Class in school Previous number of visits With whom do they spend their time Their opinion of how empty the playground is Whether or not they have easy freedom of movement Whether they like the plants or not The number of plants Which facilities are lacking The dependent variables in the questionaire for children: Reason for coming Freqeuncy of usage of the subject playground. Times when they visit the playground Amount of time they spend in the playground Who decided that they [ie. The children ] come to the playground With whom do they come to the playground With whom do they spend their time in the playground Whether or not they have easy freedom of movement Which play facilities they like the most Which game they play the most among themselves Level of sunlight in the playground Which types of plants would they choose for the playground were they given the choice The amount of noise which they recognize in the playground Their opinion on what causes the noise Whether or not they use other playgrounds Frequency of usage of other playgrounds Their opinion on the differences between the subject playground and others The kinds of activities they would like to do in the subject playground What kind of things they feel are lacking İn the playground If they had the chance to create a playground how would it look XVIII The cross tables were prepared to demonstrate the correlation between these dependent and independent variables. It is possible to sum up the results as follows: The majority of parents who bring their children to the playground are mothers and housewives. For adults the most common reason for coming to the subject playground is its proximity to their homes. This is more important for mothers than fathers as the figures illustrate. It was observed in Democracy and Zeytinburnu park that neighbours come together and while the children are playing they ( the mothers ) are able to chat and socialize. Children's reason for coming to the playground can be effected by the location. In Atasehir the children chose to come to the playground in order to be with their friends. The children in Democracy and Zeytinburnu chose to come because of the facilities present in each one. The reasons for this lie in the fact that in Atasehir the parents of these children have the financial resources to be able to send their children to other kinds of sports and social activities in and around the residential area. The children who play in the two other parks in this survey came from lower income backgrounds and consequently their parents do not have the financial resources to send them to such facilities as are enjoyed by the children of Atasehir. Although the parents in Democracy and Zeytinburnu park do not find these playgrounds well-kept and clean they still continue to bring their children because there is no other more convenient alternative available to them. The problem common to all these areas is the fouling of domestic animals. In all three playgrounds there were neither any notices present nor were there any barriers to prevent the intrusion of such pets. The faculties in all the playgrounds do not satisfy the needs of all age groups, especially the very young children (age 0-3) and the older ones (13-16.) The parents of very young children do not bring them to the playground because they find the facilities dangerous. The older children of Democracy and Zeytinburnu parks are using facilities which were not designed for them and are therefore damaging them because they do not have the opportunity to use sport and play facilities which would be more suitable for them. It has been observed that children like a large number of plants and for them to be in different varieties and colours. They seem to especially favour fruit trees and flowers. The upkeep of the plants in Zeytinburnu park was not good and thus few plants now remain since their initial planting. This has of course had the effect that children are dissatisfied to some extent because of this lack of healthy greenery. Boys also generally like games involving balls and therefore prefer clear green grass areas. The planting in the other areas looks better, however, they too need more green, open areas. Children therefore need a variety of playgrounds and more sports facilities which must of course be well looked after, so that they are able to be more creative in the playground environment. In order to do this there must be recognition on the part of XIX the government and in public opinion that playgrounds form an essential element in a child's development and must therefore be given greater importance if tommorow's youth are to be an ever more imaginative and dynamic generation.
Tez (Yüksek Lisans) -- İstanbul Teknik Üniversitesi, Fen Bilimleri Enstitüsü, 1998
Thesis (M.Sc.) -- İstanbul Technical University, Institute of Science and Technology, 1998
Keywords: Kent parkları; Oyun alanları; Toplu konutlar; Çocuk bahçesi; Playground; Urban parks; Playground; Mass houses; Playground